A Retrospective Study to Examine Healthcare Costs Related to Cardiovascular Events in Individuals with Hyperlipidemia. Issue 11 (November 2015) - Henk, Henry; Paoli, Carly; Gandra, Shravanthi
Abstract Introduction Few studies have demonstrated the cost burden of cardiovascular events (CVEs) among patients with hyperlipidemia. The primary objective of this study was to determine the mean costs associated with CVEs among patients with hyperlipidemia by follow-up time period. Secondary objectives of this study included characterizing costs by CVE type and coronary heart disease (CHD) risk. Methods This retrospective cohort study used longitudinal claims to calculate payer costs according to CHD risk level and type of CVE, during several follow-up periods (acute and short-term, comprising year 1; plus years 2 and 3). Results There were 193, 385 patients with hyperlipidemia with a CVE. Costs in the acute (30-day) period were highest (22, 404) driven by inpatient care (77%). Costs remained high (15, 133 in year 3) with ambulatory care (from 14% in acute to 37% in year 3) and pharmaceutical costs (from 2% in acute to 24% in year 3) representing a greater proportion. After second and third CVEs, acute costs were lower than for the first CVE. But in the post-acute periods, costs were higher after second and third CVEs than after first CVEs. Acute costs varied considerably by type of CVE (9149 for transient ischemic attack to 54, 251 for coronary artery bypass graft;P < 0.001), but post-acute costs were more similar across types. Costs differed by baseline CHD risk for all follow-up periods (P < 0.001), but less than by CVE type. As expected, patients without CVEs had significantly lower costs. Conclusion Among patients with hyperlipidemia, the economic burden of CVEs is substantial up to 3 years after a CVE. Costs remain high after subsequent CVEs and actually increase for non-inpatient utilization. Funding Amgen Inc.